2011
DOI: 10.1016/j.mrfmmm.2011.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Common fragile sites in colon cancer cell lines: Role of mismatch repair, RAD51 and poly(ADP-ribose) polymerase-1

Abstract: t r a c tCommon fragile sites (CFS) are specific chromosomal areas prone to form gaps and breaks when cells are exposed to stresses that affect DNA synthesis, such as exposure to aphidicolin (APC), an inhibitor of DNA polymerases. The APC-induced DNA damage is repaired primarily by homologous recombination (HR), and RAD51, one of the key players in HR, participates to CFS stability. Since another DNA repair pathway, the mismatch repair (MMR), is known to control HR, we examined the influence of both the MMR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…An important step ensuring the fidelity of this process is the assessment of sequence identity between paired strands of heteroduplex DNA (31,53). A large body of evidence has suggested that the MMR machinery plays a central role in rejecting heteroduplex DNA containing a mismatch and that this role is particularly important during repair of highly repetitive DNA and of the common fragile sites (1,3,54). Here, we demonstrated that the first MMR responder in humans, hMSH2-hMSH6, is able to recognize a mismatch within the heteroduplex region of a D-loop recombination intermediate (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…An important step ensuring the fidelity of this process is the assessment of sequence identity between paired strands of heteroduplex DNA (31,53). A large body of evidence has suggested that the MMR machinery plays a central role in rejecting heteroduplex DNA containing a mismatch and that this role is particularly important during repair of highly repetitive DNA and of the common fragile sites (1,3,54). Here, we demonstrated that the first MMR responder in humans, hMSH2-hMSH6, is able to recognize a mismatch within the heteroduplex region of a D-loop recombination intermediate (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…HCT116+3 cells, transfected with pBabe vector only, were used as control (HCT116+3 Babe). The HCT116 SiP and Babe cell lines were previously described (23). Cells were maintained in the presence of 1 µg/ml puromycin (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…Whether microsatellite instability is the cause or consequence of FHIT loss, if they are both consequences of a common cause, or if one of the events is positively selected in the presence of the other one, is not known. Of note, it has been suggested that defective MMR, which generates MSI, can also cause deletions affecting genes in CFSs [ 81 , 82 ].…”
Section: Discussionmentioning
confidence: 99%